Den sidste urnegrav fra Tombølgård – en jernaldergrav med træskrin og en bronzealder celt - Jensen, Mads Leen (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
This article presents the last of the graves excavated in 2018 at the Tombølgård cemetery site on Als. The cemetery site dates to the Early Roman Iron Age, B 1 and B 2. The site is known from a small excavation of a single urn in 1932, and from metal detector finds found between 2016 and 2018, and finally from the excavation in 2018. The grave goods from this last cremation grave from 2018 include a silver hair pin, shears, knives, and the remains of a lock for a wooden box. The box had probably contained some odd and old objects, which were found in the urn. These objects suggest that the deceased may have had a significant role in the society at the time.